Analisis dan Pemodelan Proses Bisnis Distribusi Suku Cadang Otomotif pada PT. XYZ Menggunakan BPMN - Mutia Herman; Muhammad Richie Hadiansah; Fakhri Alauddin Tarihoran; Muhammad Alvin Nurrahman; Idham Tiofandy Hasibuan; Meiranda Siregar; Muhammad Ayub Ardi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The business process of selling and procuring products at PT. XYZ still relies on manual coordination and systems that have not yet been integrated, so workflows and process traceability are not yet optimal. This research aims to analyze and model these business processes using Business Process Model and Notation (BPMN). The research method used is descriptive research through observation and document study. The research data is in the form of activity flows, the role of actors, operational documents, and information on the use of the system in the sales and product procurement process. The results show that as-is business process modeling identifies flow inefficiencies, while to-be modeling results in more structured processes, integrated with information systems, and clarifies the roles and responsibilities of actors.